Impacts of pasteurized buffalo milk on pr oliferation of Hela cells: Role of Caspase-3, Caspase-9, and P53 genes - El-Bahgy, HEK; Abulaiti, A; Soliman, MM; Althobaiti, F; Elshehawi, A; Yang, L (Journal of the Hellenic Veterinary Medical Society, 2025)
Buffalo milk is characterized by its high nutritional value, and there is a significant association between excessive consumption of commercially available buffalo milk and the development of various cancer types. The current study was designed to assess how buffalo milk affects the growth and viability of Hela cells, a cervical cancer cell line, as well as to investigate the molecular mechanism behind these effects. Pasteurized-buffalo milk was added to cells at 0% (negative control), 0.00025%, 0.0005%, 0.001%, 0.0015, 0.002%, 0.0025%, 0.005%, and positive control (H2O2) for 24 hours. Results indicated that the growth of Hela cells was notably boosted as the concentration of buffalo milk increased. The buffalo milk reduced the apoptosis of Hela cells and increased the viability of cells. Moreover, Caspase-3 and Caspase-9 activities were stimulated in treated Hela cells, and significantly increased with 0.001% of buffalo milk, compared to positive control cells. In contrast, buffalo milk treatment for 24 hours showed substantial reduction in P53 gene expression within Hela cells. In conclusion, buffalo milk increases the proliferation and viability of Hela cells by decreasing the apoptosis and cell viability of examined cells. Furthermore, it induces upregulation in Caspase-3 and Caspase-9 expressions while deactivating the expression of P53 gene.